1998
DOI: 10.1109/23.682433
|View full text |Cite
|
Sign up to set email alerts
|

Structured CsI(Tl) scintillators for X-ray imaging applications

Abstract: We are developing large-area, thick, structured CsI(Tl) imaging sensors for a wide variety of X-ray imaging applications. Recently we have fabricated structured CsI(Tl) scintillators ranging from 30 µm (16 mg/cm 2) to 2000 µm (900 mg/cm 2) in thickness and up to 15 x 15 cm 2 in area. Even 2000-µm-thick film showed well-controlled columnar growth throughout the film. Material characterization confirmed that the film is crystalline in nature and that the stoichiometry is preserved. To improve the spatial resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
145
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(149 citation statements)
references
References 9 publications
0
145
0
Order By: Relevance
“…Initially, this result would seem to have no practical impact, since back-screens are not currently used clinically due to the glass substrate of the thin-film transistor (TFT) array for digital signal readout. 25,27 If these detectors were operated as back-screens, the high attenuation of glass ($0.7 mm thick) would prevent a large percentage of x-rays from reaching the phosphor itself, 19 and hence both QDE and DQE would be compromised. Based on new research on flexible organic light-emitting diode (OLED) displays, however, TFT arrays may soon be manufactured on a plastic substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, this result would seem to have no practical impact, since back-screens are not currently used clinically due to the glass substrate of the thin-film transistor (TFT) array for digital signal readout. 25,27 If these detectors were operated as back-screens, the high attenuation of glass ($0.7 mm thick) would prevent a large percentage of x-rays from reaching the phosphor itself, 19 and hence both QDE and DQE would be compromised. Based on new research on flexible organic light-emitting diode (OLED) displays, however, TFT arrays may soon be manufactured on a plastic substrate.…”
Section: Discussionmentioning
confidence: 99%
“…47 Another extension of this work would be to model detector pixilation due to the TFT array in which the phosphor is placed in optical contact. [25][26][27] In this setting, the PSF is the convolution of the phosphor blurring function with the detector element sampling function. [48][49][50] An additional subtlety that may be modeled is the blurring of the focal spot.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal itself has a complex columnar structure that directs the optical photons down the thickness of the crystal and improves the detector resolution as compared with unstructured crystals. [1][2][3] This columnar structure also affects the point response function ͑PRF͒ of the detector in a complex manner that is difficult to model. The PRF fully describes the blurring behavior of the scintillator and is simply the image that results from x rays that are incident on the detector at a single, infinitesimally small point.…”
Section: Introductionmentioning
confidence: 99%
“…In this specific example the recorded data showed that the initial alignment (red squares/purple dotted line, 0.94 mm [18 ] radial precession) did not meet the requirement (0.52 mm [10 ]). After additional adjustments were made, the PSF measurements at different roll positions were repeated (green circles/dashed line, 0.42 mm [8 ] radial precession) and used to verify that the precession tolerance met specifications. The two data sets show that after the re-adjustment, the alignment was improved and fully met the NuSTAR calibration requirements † .…”
Section: Optics Installation and Alignmentmentioning
confidence: 99%
“…Right:Cross-sectional SEM view of microcolumnar CsI(Tl) film which was deposited on a suitable substrate. 8 The column diameter is about 10 µm on average.…”
Section: Introductionmentioning
confidence: 99%